Enhanced electrocatalytic activity of PtRu/nitrogen and sulphur co-doped crumbled graphene in acid and alkaline media - Pang, Liuqing; Miao, Yuanyuan; Bhange, Siddheshwar N.; Barras, Alexandre; Addad, Ahmed; Roussel, Pascal; Amin, Mohammed A.; Kurungot, Sreekumar; Szunerits, Sabine; Boukherroub, Rabah (Journal of Colloid and Interface Science, 2021)
The low mass activity and high price of pure platinum (Pt)-based catalysts predominantly limit their large-scale utilization in electrocatalysis. Therefore, the reduction of Pt amount while preserving the electrocatalytic efficiency represents a viable alternative. In this work, we prepared new PtRu2 nanoparticles supported on sulphur and nitrogen co-doped crumbled graphene with trace amounts of iron (PtRu2/PF) electrocatalysts. The PtRu2/PF catalysts exhibited enhanced electrocatalytic performance and stability for the hydrogen evolution reaction (HER) at pH = 0. Moreover, the prepared PtRu2/PF electrocatalyst displayed higher HER activity than commercial 20% Pt/C. The PtRu2/PF catalyst achieved a current density of 10 mA cm(-2) at an overpotential value of only 22 mV for HER, performing better activity than many other Pt-based electrocatalysts. Besides, the PtRu2/PF revealed a good performance for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in alkaline media. The PtRu2/PF catalyst recorded a current density of 10 mA cm(-2) at an overpotential of only 270 mV for OER in KOH (1.0 M) solution and an onset potential of 0.96 V vs. RHE (at 1 mA cm(-2)) for ORR in KOH (0.1 M) solution. (C) 2021 Elsevier Inc. All rights reserved.
Keywords: HER; OER; ORR; PtRu2; Sulphur and nitrogen co-doped crumbled graphene